2001
DOI: 10.1136/gut.48.6.816
|View full text |Cite|
|
Sign up to set email alerts
|

Increase in mortality rates from intrahepatic cholangiocarcinoma in England and Wales 1968–1998

Abstract: Background-The age standardised mortality rate per 100 000 population for all causes of liver tumours (International Classification of Disease 9 (ICD-9) 155) has almost doubled in England and Wales during the period 1979-1996. We further analysed the mortality statistics to determine which anatomical subcategories were involved. Methods-Mortality statistics for liver tumours of ICD-9 155, 156, and subcategories, and for tumours of the pancreas (ICD-9 157), in England and Wales were investigated from the OYce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
227
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(234 citation statements)
references
References 16 publications
4
227
0
3
Order By: Relevance
“…2,3 Because of the late clinical presentation, CC is in most cases fatal by the time it becomes clinically evident. 4 From a general viewpoint, prognosis of CC is also poor, with a 5-year survival rate of less than 5%.…”
mentioning
confidence: 99%
“…2,3 Because of the late clinical presentation, CC is in most cases fatal by the time it becomes clinically evident. 4 From a general viewpoint, prognosis of CC is also poor, with a 5-year survival rate of less than 5%.…”
mentioning
confidence: 99%
“…Studies from the United States of America (USA) and the United Kingdom (UK) have shown marked increases in mortality from primary liver cancers in the last two decades of the 20th century (Taylor-Robinson et al, 1997;El-Serag and Mason, 1999;Patel, 2001;Taylor-Robinson et al, 2001;Shaib et al, 2004). While there have been incidence data reported from the USA, there has been no report of recent trends (last 30 years) in incidence from the UK.…”
mentioning
confidence: 99%
“…Isso fortaleceria a hipó-tese de um padrão real de redução do coeficiente de mortalidade por câncer de fígado nas regiões Sudeste e Sul, ressaltando-se a diferença entre os sexos, com declínio dos coeficientes para o feminino, evento este restrito às regiões mencionadas e, aumento para o masculino, notório em todas as regiões. Diferentemente de outros estudos que atribuem o aumento dos casos de câncer de fígado ao aumento da frequência de óbitos por carcinoma hepatocelular ou colangiocarcinoma 4,25 , é difícil avaliar se o incremento dos coeficientes de mortalidade no Brasil também se deve a este fato, pois a maioria dos óbitos na série histórica analisada tem sido codificada como neoplasia maligna do fígado não especificada. A despeito do aumento global do diagnóstico e identificação desses tumores no Brasil, parece persistirem dificuldades inerentes à especificação dos mesmos à luz da CID-10.…”
Section: Métodosunclassified